The impact of off-centred groups on an archer`s score - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Archers frequently lose score by having their sights set incorrectly, resulting in off-centre groups on the target and lower scores than would otherwise have been possible. The archer`s group on the target has been modelled using a normal distribution where the size of the archer`s group depends upon the archer`s skill level and target distance. Off-centred groups were modelled by varying the arrow positions on the vertical axis and the score loss at the usual competition distances using a Monte Carlo technique. A method of using the centroid of each three or six-arrow end is used to optimise the sight setting and minimise score loss, realising that this is done using data from a very limited number of shots. It is best to correct for only a portion of the error for each end, rather than for the full error.